The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3390/ani12192545
|View full text |Cite
|
Sign up to set email alerts
|

What Happens in Male Dogs after Treatment with a 4.7 mg Deslorelin Implant? II. Recovery of Testicular Function after Implant Removal

Abstract: Although deslorelin slow-release implants are widely used in the clinic, detailed published information about the recovery of testosterone concentrations (T), semen quality, and testicular and prostatic volume (TV, PV) after treatment is still missing. This article aims to characterize changes during restart after a five-months treatment and subsequent implant removal. Seven male Beagle dogs were treated with deslorelin (treatment group, TG), and three saline-treated dogs served as controls (CG). Deslorelin im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
8
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 41 publications
4
8
1
Order By: Relevance
“…As expected, high testosterone concentrations were more likely associated with a more progressed recovery of spermatogenesis or even restoration in the majority of seminiferous tubules whereas the early time points of castration were associated with an arrest on spermatogonia and spermatocytes as the most developed germ cells. Diff erent to our recent study where fi rst spermatozoa were found 7 to 10 weeks after implant removal in all 6 dogs [ 15 ] , only 2 dogs castrated 10 weeks after removal had fully elongated spermatids in their testis allowing for the assumption that they might have had spermatozoa in ejaculates. In all other dogs except for those that returned earlier, presence of spermatozoa in ejaculates seems unlikely.…”
Section: Week(s) After Sri Removal N Mean ± Sd [Range]contrasting
confidence: 82%
See 4 more Smart Citations
“…As expected, high testosterone concentrations were more likely associated with a more progressed recovery of spermatogenesis or even restoration in the majority of seminiferous tubules whereas the early time points of castration were associated with an arrest on spermatogonia and spermatocytes as the most developed germ cells. Diff erent to our recent study where fi rst spermatozoa were found 7 to 10 weeks after implant removal in all 6 dogs [ 15 ] , only 2 dogs castrated 10 weeks after removal had fully elongated spermatids in their testis allowing for the assumption that they might have had spermatozoa in ejaculates. In all other dogs except for those that returned earlier, presence of spermatozoa in ejaculates seems unlikely.…”
Section: Week(s) After Sri Removal N Mean ± Sd [Range]contrasting
confidence: 82%
“…Week ting that the "true" testosterone reference range might be even wider or results might also be dependent on the test used. Samples in this study were run in a RIA that we used repeatedly before, making our results comparable to our earlier studies [5,13,15,16]. Nevertheless, testosterone in TG and CG did not differ significantly.…”
Section: Week(s) After Sri Removal N Mean ± Sd [Range]supporting
confidence: 80%
See 3 more Smart Citations